Bridging the Gap Between Business to Business (B2B) and Business to Consumer (B2C): Thought Leadership in Industrial Marketing-A Systematic Review of the Literature and Propositions. - Firmanjaya Saputra, Anggi; Wardi, Yunia; Thaib, Ilham (Universitas Negeri Padang, 2024)
This article examines the important role of thought leadership in bridging the gap between business to business (B2B) and business to consumer (B2C) in the context of industrial marketing. By conducting a systematic literature review of 20 related articles, this research identifies key factors such as transformational leadership, knowledge-oriented leadership, ethical leadership, adaptability, collaboration, and innovation as important elements in designing effective leadership strategies. Findings from various studies highlight the need for a holistic and adaptive approach in managing differences between B2B and B2C, and formulate propositions that can form the basis for future research. This article provides important insights for practitioners and academics in understanding how thought leadership can act as an effective link between these two different business models.